2013
DOI: 10.1016/j.pec.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between social support and stroke survivors’ health-related quality of life—A systematic review

Abstract: Attention should be paid to promoting social support on the short and long term. Further research is needed to clarify the influence of social support type and source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 35 publications
3
70
1
3
Order By: Relevance
“…Social support can be instrumental emotional, or informational [45]. Studies have shown that social support is a determinant of HRQOL [31,41,34,45].…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support can be instrumental emotional, or informational [45]. Studies have shown that social support is a determinant of HRQOL [31,41,34,45].…”
Section: Social Supportmentioning
confidence: 99%
“…Studies have shown that social support is a determinant of HRQOL [31,41,34,45]. Furthermore, a review by Reblin and…”
Section: Social Supportmentioning
confidence: 99%
“…LSAT is generally agreed to be a broad, multidimensional concept with both subjective and objective components [7]. For our study, LSAT refers to the universal measure of quality of life which denotes a general subjective assessment of an individual's life and does not inevitably represent satisfaction with all aspects of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Social support has been recognized as an important determinant of health-related quality of life in stroke survivors [6]. The relationship between various types of social support such as emotional, instrumental, or informational support and quality of life is inconsistent [6].…”
Section: Introductionmentioning
confidence: 99%